Shell Biorefinery: Dream or Reality?. Issue 38 (3rd August 2016) - Chen, Xi; Yang, Huiying; Yan, Ning
Abstract: Shell biorefinery, referring to the fractionation of crustacean shells into their major components and the transformation of each component into value‐added chemicals and materials, has attracted growing attention in recent years. Since the large quantities of waste shells remain underexploited, their valorization can potentially bring both ecological and economic benefits. This Review provides an overview of the current status of shell biorefinery. It first describes the structural features of crustacean shells, including their composition and their interactions. Then, various fractionation methods for the shells are introduced. The last section is dedicated to the valorization of chitin and its derivatives for chemicals, porous carbon materials and functional polymers. Abstract : Prawn to be wild : Waste shells are disposed of in large quantities worldwide every year. Rather than treating this underexploited resource as waste, shell biorefinery provides a potentially ecological and economical solution to valorize shells as a source of useful chemicals and materials.